The Physical Characteristics of Handmade Soap Made Up Using Used Cooking Oil - MHD ZOL, MOHD ZAROUL AFIQ; MOHD RUS, ANIKA ZAFIAH (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Waste cooking oil can be harmful to the environment if it is not disposed correctly. One of the ways to reuse the waste cooking oil is by using it to make handmade soap. The main aim of this research is to produce soaps with different kinds of additives. The number of soap samples that have been made in this research is 12 with different concentrations and using two kinds of additives which are lemon peel and cinnamon powder. Three kinds of tests have been used to find the physical properties of the soap samples which are hardness test, pH test and swelling test. The hardness test shows that soaps with the highest concentration of additives have the least hard surface and higher stirring time helps in decreasing the hardness of the surface of the soap. Based on the results, UC1510 have the least hardness and it also have the same hardness as the commercial Dettol bar soap. The pH value of the soap is predetermined by the type of additive used. The concentration will not give any difference to the pH value as shown that all the lemon-based soaps have a pH value of 10 and cinnamon-based soap have a pH value of 9. UL1510 soap sample shows the highest absorption of sugar solution and vinegar solution. There are no reactions when soap encountered brine and oil. A brochure has been prepared which contain the Cold Process procedure of soap production with some precaution when producing the soap for the usage of small and medium enterprises (SME). Based on the results, UC1510 is the best soap for usage as it has least hardness of its surface and a pH value of 9 which is neutral.